Liquid-based cytology features of pancreatic acinar cell carcinoma: comparison with other non-ductal neoplasms of the pancreas - Minji Kwon; Seung-Mo Hong; Kyoungbun Lee; Haeryoung Kim (Korean Society of Pathologists & the Korean Society for Cytopathology, 2024)
Background Acinar cell carcinoma (ACC) is a rare malignant epithelial neoplasm, which shares many cytomorphological features with other non-ductal pancreatic neoplasms such as pancreatic neuroendocrine neoplasm (PanNEN) and solid-pseudopapillary neoplasm (SPN). Due to the relative rarity of these tumors, pathologists are less familiar with the cytological features, especially on liquid-based cytology (LBC) which has been relatively recently introduced for endoscopic ultrasound-guided fine needle aspiration specimens. Methods We evaluated the detailed cytological features of 15 histologically confirmed ACC (7 conventional smears [CS], 8 LBC), and compared them with the LBC features of SPN (n = 9) and PanNEN (n = 9). Results Compared with CS, LBCs of ACC demonstrated significantly less bloody background. All ACCs demonstrated prominent nucleoli and macronucleoli on LBC. On comparison with the LBC features of SPN and PanNEN, most ACCs demonstrated a necrotic background with apoptotic debris while PanNEN and SPN did not show these features. Acinar structures were predominantly observed in ACC, while frequent pseudopapillary structures were seen only in SPN. Prominent nucleoli and macronucleoli were only seen in ACC. Conclusions ACC had characteristic cytological features that could be observed on LBC preparations, such as high cellularity, necrotic/apoptotic background, nuclear tangles, acinar arrangement of cells, and macronucleoli. These findings also help distinguish ACC from PanNEN and SPN on LBC. It is important to be familiar with these features, as an accurate diagnosis on endoscopic ultrasound-guided fine needle aspiration cytology would have impact on the management of the patient.